Perspectives of Relations between School and Parents from the Middle Ages to the Reformation - Vidmar, Tadej (Pedagogika, 2015)
Author analyses some perspectives and interpretations of relations between school and parents in the past. He points out how they were developing in the Middle Ages and in the time of Reformation. In that time cooperation of parents and a school was understood essentially different as today. In the Middle Ages the relation between parents and a school was clear and mostly non-problematic, at least regarding the contents, methods and objectives of education. Relations inside the school were an image of relations inside the family. In the time of Reformation status was not essentially different, still educators as Johannes Sturm began more intensively to think about meaning of cooperation between a school and a family.